(untitled) (Journal of Forensic Medicine & Toxicology, 2026)
Sexual dimorphism in bones is essential in identifying unidentified bodies from skeletal remains. The manubrium and sternum have a high rate of recovery (over 59%), which makes these bones particularly useful. The accuracy of sex deter mination can be increased by taking measurements such as the width of various ribs into account. Our primary objective was to correlate the sexual dimorphism of the sternum and fourth, fifth and sixth ribs with osteometric measurements and sternal index in the South Indian population. A total of 214 patients, consisting of 107 males and 107 females, were included in the study. The left fourth rib superior-inferior height (SIH) was the best predictor for sex determination, fol lowed by the sternal area, right fourth rib SIH and the combined length of the manubrium and sternal body. Among ster nal measurements, the sternal area (SA) showed the highest degree of sexual dimorphism, correctly classifying 84.11% of males and 90.65% of females, and the overall correct classification rate was 87.38%. The combined manubrium and sternal body length (CL) were also correctly classified in 85.05% of males and 88.79% of males, and the overall classifica tion accuracy rate is 86.92%. Analysis revealed that the left fourth rib superior-inferior height (SIH) exhibited a correct classification rate of 92.52% for males and 84.11% for females at a cut-off value of 1.39 cm. The overall classification rate was found to be 88.32%.